Capturing the Digital Age: The Impact of Risks of Technological Advancements in Auditing on Students' Views - Johanes, Kristallisya Alexandra; Surifran, Vicky Putra; Gunawan, Samuel Octavianus; Tjun Tjun, Lauw; Marpaung, Elyzabet Indrawati (COMPETITIVE, 2024)
Technological developments in the world have experienced extraordinary progress in the last few decades, fundamentally changing the way we live, work and interact. Technological developments have had a significant impact on the audit profession, changing the way auditors conduct audits and provide independent opinions on financial reports. So this research aims to analyze accounting students' views on technological advances in the audit field. The population of this research is students who are taking a study program in accounting at Maranatha Christian University. With a sample size of 65 respondents using purposive sampling. The data collection technique used is a questionnaire and will be processed using Stata software. The results of this research show that aspects of awareness and skills have a positive effect on knowledge, and vice versa.